Analisis Model Mental Siswa pada Materi Hidrolisis Garam di Klaten - Rahma Esi Andina; Achmad Ridwan; Yuli Rahmawati (Jurnal Riset Pendidikan Kimia (JRPK), 2017)
The aim of this study is to analyze students’ mental model of hydrolysis concepts. The subjects of this study were the best science class students of a public senior high school at Klaten. This research employed ethnography as a research methodology. Data collection techniques were in-depth interviews, classroom observation, and reflective journals. The results showed that the students built mental models based on their understanding and experience that influenced by the environment around the students. The students’ learning is influenced by the students’ characteristics of politeness, empathy communication, and value of the teacher is always right. The students’ mental models of hydrolysis concept were divided into understanding and misconceptions. Teacher’s understanding of students’ mental model will help the teacher in developing meaningful learning experiences. Keywords: Mental Model, Ethnography, Hydrolisis